ANALISIS PROSEDUR KERTAS KERJA AUDIT BEBAN PADA PT. DEALER MERCEDES BENZ OLEH KAP KPS - Hanif, Diva Aulia; Suryaningrum, Diah Hari (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The purpose of this research is to analyze the expense working paper procedure of PT Mercedes Benz Dealer which has been determined by KAP KPS. The method used in this research is descriptive qualitative using a case study approach. The data sources used in the research are primary data through interviews with one of the auditors at KAP KPS and secondary data. The procedures carried out in the load work papers consist of the Leadsheet Procedure, 12 Column Analysis Procedure, Predictive Salary Test Procedure, and Vouching Procedure. The results showed that the expense working paper procedures had been carried out in accordance with audit standards and there was no material misstatement of the presentation of expenses of PT Mercedes Benz Dealer